2017
DOI: 10.4103/1735-5362.217430
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation, docking and molecular dynamic simulation of some novel diaryl urea derivatives bearing quinoxalindione moiety

Abstract: In this study a series of diarylurea derivatives containing quinoxalindione group were biologically evaluated for their cytotoxic activities using MTT assay against MCF-7 and HepG2 cell lines. Antibacterial activities of these compounds were also evaluated by Microplate Alamar Blue Assay (MABA) against three Gram-negative (Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi), three Gram-positive (Staphylococcus aureus, Bacillus subtilis and Listeria monocitogenes) and one yeast-like fungus (Candida a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…42 Because of the therapeutic importance of LFB, the chemistry of its binding to different organic targets has been a subject of considerable research. 43,44 Owing to the presence of multiple N-based functional groups, LFB molecules can be readily immobilized on a metal substrate for immersible biosensors or on gold nanoparticle (AuNP) nanocarriers for targeted controlled drug delivery (CDD), as shown recently for various highly toxic chemotherapeutic drugs, like gemcitabine, 45 dabrafenib, 46 azacitidine and decitabine. 47 However, the CT reaction of LFB has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…42 Because of the therapeutic importance of LFB, the chemistry of its binding to different organic targets has been a subject of considerable research. 43,44 Owing to the presence of multiple N-based functional groups, LFB molecules can be readily immobilized on a metal substrate for immersible biosensors or on gold nanoparticle (AuNP) nanocarriers for targeted controlled drug delivery (CDD), as shown recently for various highly toxic chemotherapeutic drugs, like gemcitabine, 45 dabrafenib, 46 azacitidine and decitabine. 47 However, the CT reaction of LFB has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the global health problems. Significant progress has been observed in cancer research in the last ten years(27). Considering the adverse complications and resistance to the current chemotherapeutic agents, development of more efficient anticancer agents with less harm has remained as an important subject in drug design(27).…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been observed in cancer research in the last ten years(27). Considering the adverse complications and resistance to the current chemotherapeutic agents, development of more efficient anticancer agents with less harm has remained as an important subject in drug design(27). The findings of this study provide an integral part of the pre-clinical investigation of our compounds that can be further developed as anticancer agents against tumors, with excellent oral absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoxaline, a bioisostere, is considered as an important nucleus for many anticancer drugs, 25,26 and also quinoxaline derivatives were reported to exhibit potent VEGFR-2 inhibitory activity. 27,28 Based on these facts, M. M. Alanazi et al reported 3-methylquinoxaline derivatives as VEGFR-2 inhibitors. 29 Initially, the synthesized compounds were investigated for their anticancer activity wherein N-t -butylbenzamide derivative 15 (Fig.…”
Section: Introductionmentioning
confidence: 98%